Specifics of Amending and Terminating the Contract for the Provision of Tourist Services - Haykyants, Armen; Saghoyan, Yeva (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article discusses the specific features of amending and terminating contracts for the provision of tourism services. In particular, by comparing the regulations enshrined in the Law of the Republic of Armenia "On Tourism" and international documents governing the sector with the provisions of the RA Civil Code regarding unilateral amendment and termination of contracts, the author concludes that, due to the fixed-term nature of such contracts and the fact that they imply one-time execution, applying the judicial procedure for unilateral amendment and termination, as provided by the Civil Code, is not appropriate in this context. Instead, the author proposes to define by law the scope of essential breaches committed by either party that may serve as grounds for termination of the contract, as well as the most typical manifestations of significant changes in circumstances. In the event such grounds arise, it is suggested to grant the interested party the right to unilaterally terminate the contract out of court by operation of law. At the same time, it is proposed to establish rules for the distribution of expenses between the parties in such cases- in particular, the reimbursement of the cost of the service for organizing the provision of tourism services. Using the example of a contract for the organization of tourism service provision, the author also addresses certain key issues related to the correlation between the institutions of unilateral contract termination and unilateral refusal to perform the contract.